Perception of Medical Assistance in Dying Among Asian Buddhists Living in Montreal, Canada. (August 2022) - Dorji, Nidup; Lapierre, Sylvie; Dransart, Dolores Angela Castelli
In the Western world including Canada, grievous and irredeemable health conditions, which cause unbearable suffering, has given support to the legalization of medical aid in dying (MAiD). It is unknown how Asian Buddhists who are in contact with the Western culture perceive MAiD. In this qualitative study, 16 Asian Buddhists living in Montreal took part in a semi-structured interview. Contrary to general findings in the literature, religious affiliation do not always determine moral stances and practical decisions when it comes to MAiD. Some participants were willing to take some freedom with the doctrine and based their approval of MAiD on the right to self-determination. Those who disapproved the use of MAiD perceived it as causing unnatural death, creating bad karma, and interfering with a conscious death. End-of-life (EoL) care providers have to remain sensitive to each patient's spiritual principles and beliefs to understand their needs and choices for EoL care.